Admission avoidance and early discharge of acute hospital admissions: an accident and emergency based scheme - Hardy, C; Whitwell, D; Sarsfield, B; Maimaris, C (Emergency medicine journal : EMJ, 2001)
Objectives—To validate an accident and emergency (A&E) based approach to assisting early discharge or avoiding admission to acute hospital beds by means of two separate teams, one in hospital and the other in the community, working closely together at the interface between primary and secondary health care. Design—A purpose designed admission avoidance (AA) team was established in the A&E department, and a target group of patients identified whose admissions might be avoided or curtailed. A rapid response community team (RRCT) based in Cambridge was also established to provide basic health care to patients in their homes after discharge from hospital. The key elements of the project were rapid assessment, careful selection of patients, early decision making at senior level, and close liaison with the community team. Results—During the first year (1999) of the project the AA team assessed 785 patients and 257 patients were eventually discharged home to the care of the RRCT. Of these, 149 patients (58%) were comparable to a historical control group (from 1997/98), with regard to their demographic and clinical characteristics and care needs, and had an average length of hospital stay of 1.7 days compared with 6.3 days for the control group. The remaining 108 patients were not directly comparable but were supported by the teams because the benefits were clear and exclusion would have been unethical. These patients had an average length of stay of seven days. The readmission rate was 3 of 257(1.2%) for the intervention group and 8 of 531(1.5%) for the control group. A limited patient satisfaction survey among patients cared for at home revealed that 97% of patients were “satisfied to very satisfied” with the care provided. The RRCT had also looked after an additional 194 patients from other sources (total = 451), including postoperative orthopaedic early discharges from an adjacent hospital. The average length of care at home by the RRCT for all 451 patients was 6.6 days. The annual cost of the two teams was £113 900. Conclusions—These results indicate that an A&E based approach to the identification of patients suitable for short-term domiciliary support that aims rapidly to restore previous levels of independence, can reduce the burden of acute admissions to hospital without reducing quality of care or patient satisfaction. The scheme has now been established on a permanent basis and extension of this strategy to other patient groups is under evaluation.